The Effectiveness of the Leaf Extract of Jati Belanda (Guazuma ulmifolia Lamk) as Dengue Antiviral In Vitro - Yani Dwi Pratiwi; Leli Saptawati; Siti Marufah (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Introduction: Dengue Haemorrhagic Fever is one of a serious disease in the world because it can cause death. During all these years, DHF in Indonesia only treated by symptomatic and supportive therapy. The purpose of this study was to determine the effectiveness of Jati Belanda leafs extracts as antiviral dengue in vitro. Methods: The method used is pure experimental research and the research design method is post test only control group design. The subject is dengue virus serotype 2 strain New GuineaC (DENV2 NGC) obtained from the Laboratory of Virology and Molecular Biology Department of Microbiology, Faculty of Medicine, University of Indonesiaand this research was started from June until November 2016. The independent variables in this study is the concentration of Jati Belanda leafs extracts obtained from Pharmaceutical Laboratory of Faculty Pharmacy, Gadjah Mada University and dependent variable are infectivity value and viability value. The collected data are presented in tables. Results:In concentration 40 g/ml, the infectivity value is 12.6% and the viability value is 91.4%. Conclusions: The leaf extracts of Jati Belanda is potentially effective as antiviral dengue. Keywords: dengue, Jati Belanda extract, antivirus, DHF